Mechanical properties of rosemary (rosmarinus officinalis l.) stalks (2013)
Rosemary is an aromatic herb exported by Colombia. It is a perennial aromatic bush that can grow up to 2 m high. Its leaves are narrow, thin, shiny and strongly scented; the stems are woody and resinous, branched and slightly bitter. For harvesting, it should be cut manually, plant by plant, however product damage may occur during this process as the collector is pushing the branches to make the cut or when cut stems are placed in transport baskets. Tests were carried out on romero stalks to investigate the physical and rheological characteristics in order to make recommendations for harvest and post-harvest operations and to find design parameters for harvesting tools. The following rheological tests were performed: unidirectional compression, cutting, bending and tension of the bunches of stems, the manipulated structures. It was found that the compression forces that result in unrecoverable deformations are really small, approximately 2 N. The cutting force needed to fracture the bundle at the point of harvest is 30 to 50 N on average, depending on whether it is in the middle or at the base. The mechanical behavior of rosemary leaves corresponds to a viscoelastic, anisotropic and highly variable material.